Current Treatment Regimens and Promising Molecular Therapies for Chronic Hepatobiliary Diseases - Marilena Durazzo; Arianna Ferro; Victor Manuel Navarro-Tableros; Andrea Gaido; Paolo Fornengo; Fiorella Altruda; Renato Romagnoli; Søren K. Moestrup; Pier Luigi Calvo; Sharmila Fagoonee (Biomolecules)
Chronic hepatobiliary damage progressively leads to fibrosis, which may evolve into cirrhosis and/or hepatocellular carcinoma. The fight against the increasing incidence of liver-related morbidity and mortality is challenged by a lack of clinically validated early-stage biomarkers and the limited availability of effective anti-fibrotic therapies. Current research is focused on uncovering the pathogenetic mechanisms that drive liver fibrosis. Drugs targeting molecular pathways involved in chronic hepatobiliary diseases, such as inflammation, hepatic stellate cell activation and proliferation, and extracellular matrix production, are being developed. Etiology-specific treatments, such as those for hepatitis B and C viruses, are already in clinical use, and efforts to develop new, targeted therapies for other chronic hepatobiliary diseases are ongoing. In this review, we highlight the major molecular changes occurring in patients affected by metabolic dysfunction-associated steatotic liver disease, viral hepatitis (Delta virus), and autoimmune chronic liver diseases (autoimmune hepatitis, primary biliary cholangitis, and primary sclerosing cholangitis). Further, we describe how this knowledge is linked to current molecular therapies as well as ongoing preclinical and clinical research on novel targeting strategies, including nucleic acid-, mesenchymal stromal/stem cell-, and extracellular vesicle-based options. Much clinical development is obviously still missing, but the plethora of promising potential treatment strategies in chronic hepatobiliary diseases holds promise for a future reversal of the current increase in morbidity and mortality in this group of patients.